The increase of efficiency of application of arc covered-electrode welding for the repair of magnetized pipelines; Fixing Pipeline Problems - Kiselev A. S. Aleksey Sergeevich; Gordynets A. S. Anton Sergeevich; Saraev Yu. N.; Golikov N. I. (2014, 2014)
The use of DC for electrode-arc welding of pipelines is, in some cases, difficult or impossible due to the magnetic blowout that is a consequence of prior inspection by magnetic-flux pigs. The induced magnetic field as a consequence of the passage of such tools can reach 0.1 Tesla. To remove this effect, specialized equipment is required, such as that provided by PKNT, LABS-7K, AURA-7001-3, etc., although the result of such operations is often characterized by low efficiency. Specially trained staff are required, and the installation the equipment on welded pipes is time-consuming and costly. To avoid these shortcomings, an innovative solution for the problem of arc welding of magnetized pipes is proposed that uses alternating current with a rectangular wave form. The algorithm of switching current in the welding circuit allows the exclusion of arc breaks, and can stabilize the weld’s position and quality when there is an induced magnetic field in weld zone of up to 0.1 Tesla. A semiconductor current switch has been designed for inclusion in the welding circuit.Experience of the use of this technical solution by pipeline-construction contractors has proved the resulting increase of efficiency during pipe-welding and repair work.